The Synthetic Hand. Design Research Through Hand Drawing (diségno, 2023)
Starting from Henri Focillon’s famous essay Eloge de la main [1939] and, more recently, Tim Ingold’s book Making: Anthropology, Archaeology, Art and Architecture [2013], with the support of philosophical and anthropological considerations, the paper aims to investigate the present relevance of hand drawing, not as a mere method of representation but more properly as a method of design. The argument focuses, in the first instance, on three questions of correspondence: the hand as action and knowledge; the hand as expression and language; and the hand as a synthesis of architectural making. The aim is to demonstrate how research on and of the project is directly influenced by research on drawing, taking as case studies three master theses in architectural and urban design carried out from 2019 to 2023 at the Department of Architecture, University of Florence, through hand drawing, both in the investigation and restitution phases. The project is here intended as the result of a sequence of choices oriented toward the interpretation of places. Hand drawing has the characteristic of being able to reflect and, at the same time, control this process, according to continuous learning, always being aware of the real facts.
Keywords: hand drawing; architectural composition; design as research; language; place